An Atg9-containing compartment that functions in the early steps of autophagosome biogenesis - Mari, Muriel (The Rockefeller University Press, 2010)
Eukaryotes use the process of autophagy, in which structures targeted for lysosomal/vacuolar degradation are sequestered into double-membrane autophagosomes, in numerous physiological and pathological situations. The key questions in the field relate to the origin of the membranes as well as the precise nature of the rearrangements that lead to the formation of autophagosomes. We found that yeast Atg9 concentrates in a novel compartment comprising clusters of vesicles and tubules, which are derived from the secretory pathway and are often adjacent to mitochondria. We show that these clusters translocate en bloc next to the vacuole to form the phagophore assembly site (PAS), where they become the autophagosome precursor, the phagophore. In addition, genetic analyses indicate that Atg1, Atg13, and phosphatidylinositol-3-phosphate are involved in the further rearrangement of these initial membranes. Thus, our data reveal that the Atg9-positive compartments are important for the de novo formation of the PAS and the sequestering vesicle that are the hallmarks of autophagy.